Guinea Pig Oxygen-Sensing and Carotid Body Functional Properties - Gonzalez-Obeso, Elvira; Docio, Inmaculada; Olea, Elena; Cogolludo, Angel; Obeso, Ana; Rocher, Asuncion; Gomez-Niño, Angela (Frontiers in Physiology, 2017)
Mammals have developed different mechanisms to maintain oxygen supply to cells in response to hypoxia. One of those mechanisms, the carotid body (CB) chemoreceptors, is able to detect physiological hypoxia and generate homeostatic reflex responses, mainly ventilatory and cardiovascular. It has been reported that guinea pigs, originally from the Andes, have a reduced ventilatory response to hypoxia compared to other mammals, implying that CB are not completely functional, which has been related to genetically/epigenetically determined poor hypoxia-driven CB reflex. This study was performed to check the guinea pig CB response to hypoxia compared to the well-known rat hypoxic response. These experiments have explored ventilatory parameters breathing different gases mixtures, cardiovascular responses to acute hypoxia, in vitro CB response to hypoxia and other stimuli and isolated guinea pig chemoreceptor cells properties. Our findings show that guinea pigs are hypotensive and have lower arterial pO2 than rats, probably related to a low sympathetic tone and high hemoglobin affinity. Those characteristics could represent a higher tolerance to hypoxic environment than other rodents. We also find that although CB are hypo-functional not showing chronic hypoxia sensitization, a small percentage of isolated carotid body chemoreceptor cells contain tyrosine hydroxylase enzyme and voltage-dependent K+ currents and therefore can be depolarized. However hypoxia does not modify intracellular Ca2+ levels or catecholamine secretion. Guinea pigs are able to hyperventilate only in response to intense acute hypoxic stimulus, but hypercapnic response is similar to rats. Whether other brain areas are also activated by hypoxia in guinea pigs remains to be studied.